2019
DOI: 10.15386/mpr-1521
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal evaluation using a non-invasive imaging method (ultrasonography)

Abstract: The periodontal disease and gingival bleeding are highly prevalent in the adult population worldwide. The World Health Organization (WHO) data shows that 90–100% of the 34-year-old adults present gingival inflammation. Therefore, an investigation method is required to allow the assessment of the periodontal disease as well as the monitoring of the evolution of the gingival inflammation after periodontal treatments. Non-invasive and operator-independent methods for periodontal examination are necessary for diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…(7) Compared with laser Doppler flowmetry, Doppler ultrasound measurement offers real-time diagnosis as well as high reproducibility that allows monitoring oral microcirculation changes over time; metal constructions and/or implants do not limit studies of blood flow in the gingiva or tooth pulp. (8) Previously, we and others (9)(10)(11)(12)(13)(14) have reported that ultrasound imaging has major value in oral health and can improve the limitations of conventional methods. (15,16) Ultrasound offers visualization of anatomical features including the alveolar bone (AB), alveolar bone crest (ABC), cementoenamel junction (CEJ), gingival margin (GM), gingival thickness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Compared with laser Doppler flowmetry, Doppler ultrasound measurement offers real-time diagnosis as well as high reproducibility that allows monitoring oral microcirculation changes over time; metal constructions and/or implants do not limit studies of blood flow in the gingiva or tooth pulp. (8) Previously, we and others (9)(10)(11)(12)(13)(14) have reported that ultrasound imaging has major value in oral health and can improve the limitations of conventional methods. (15,16) Ultrasound offers visualization of anatomical features including the alveolar bone (AB), alveolar bone crest (ABC), cementoenamel junction (CEJ), gingival margin (GM), gingival thickness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive techniques to image gingival soft tissues are not currently available in dentistry. Bi-dimensional ultrasound (2D US) imaging has already shown great potential for evaluating periodontal soft-tissue structures [2][3][4][5]. Lin et al demonstrated that periodontal probing depths could be measured with photoacoustic imaging [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that patients diagnosed with MS have a disrupted dermis, due to alteration of collagen fiber structure, that can be assessed using ultrasound examination; diffuse and impaired collagen matrix is responsible for skin frailty and low mechanical strength [ 9 ]. Ultrasound applications in the maxillofacial area include investigation of lymph nodes, salivary glands, and benign and malignant tumors and monitoring of soft tissue healing, inflammation and degenerative processes, and anatomy and physiology of dento-periodontal dynamics [ 10 , 11 ]. HFU finds its applications in the diagnosis of pigmented lesions, autoimmune and degenerative diseases, and benign and malignant tumors [ 12 ], but also in the monitoring and controlling of the aging process [ 13 ], tissue healing, and regenerative processes [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%